All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 140002 by mohammad17 last updated on 03/May/21
Answered by MJS_new last updated on 03/May/21
∫x22ln1+1−x2xdx=[t=1+1−x2x→dx=−x21−x21+1−x2dt]=−4∫t2(t2−1)(t2+1)4lntdt=[byparts]=4t33(t2+1)3lnt−43∫t2(t2+1)3dt=∫t2(t2+1)3dt=[Ostrogradski′sMethod]=t(t2−1)8(t2+1)2+18∫dtt2+1=t(t2−1)8(t2+1)2+18arctant=−t(t2−1)6(t2+1)2+4t33(t2+1)3lnt−16arctant==−x1−x212+x36ln1+1−x2x−16arctan1+1−x2x+C⇒answerisπ24
Commented by mohammad17 last updated on 03/May/21
thankyousir
Terms of Service
Privacy Policy
Contact: info@tinkutara.com